Law Enforcement of Domestic Violence Cases Reviewed from Law No. 23 of 2004 concerning the Elimination of Domestic Violence (Case Study at the Medan Police PPA Unit) - Haris Setiawan; Zaid Alfauza Marpaung (Journal Equity of Law and Governance, 2024)
This research aims to analyze the implementation of law the challenges faced by the Medan Police in enforcing laws against domestic abuse crimes. Two types of data were used in this study: primary and secondary. The primary data was obtained through an in-person interview with Mrs. Shitta Syadhira Ayu, the Assistant Investigator of the Medan Police PPA Unit. Books, magazines, articles, papers, and statutory regulations especially those pertaining to the topics under discussion all constitute sources of secondary data. The study's findings clarify how the Medan Police's response to domestic abuse crimes included both repressive and preventive measures and the obstacle factors in law enforcement for criminal acts of domestic violence at the Medan Police are obstacles in penal mediation and obstacles in the legal process. Obstacles in resolving criminal acts of domestic violence through legal channels, namely the collection of initial evidence and the attitude of the victim himself.